2008
DOI: 10.1016/j.rmed.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in symptom severity and health status impairment between patients with pulmonary and pulmonary plus extrapulmonary sarcoidosis

Abstract: There are significant and clinically relevant differences in the severity of symptoms, restrictions of activities of daily living and impairment of health status between the patients with isolated pulmonary and pulmonary plus extrapulmonary sarcoidosis. Patients with pulmonary plus extrapulmonary sarcoidosis are more impaired in all these categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 18 publications
3
48
2
4
Order By: Relevance
“…It was shown that those patients with pulmonary and extrapulmonary sarcoidosis reported higher fatigue levels than those with only the lungs affected. This has also been shown by Gvozdenovic et al 11 and suggests a possible additive effect to the symptom of fatigue. Furthermore, not only the lo- calization but also the burden of the disease, seen as numbers of affected organs, showed an influence on the level of fatigue, as patients with 3 or more affected organs reported significantly more fatigue than those with fewer than 3 affected organs.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It was shown that those patients with pulmonary and extrapulmonary sarcoidosis reported higher fatigue levels than those with only the lungs affected. This has also been shown by Gvozdenovic et al 11 and suggests a possible additive effect to the symptom of fatigue. Furthermore, not only the lo- calization but also the burden of the disease, seen as numbers of affected organs, showed an influence on the level of fatigue, as patients with 3 or more affected organs reported significantly more fatigue than those with fewer than 3 affected organs.…”
Section: Discussionsupporting
confidence: 75%
“…10 The affected organs might be of critical importance since patients with pulmonary and extrapulmonary disseminated sarcoidosis have higher fatigue levels than patients with pulmonary sarcoidosis. 11 Comorbidity may contribute to fatigue levels. Examples include restless legs syndrome, which leads to disturbed and superficial sleep with subsequent fatigue, insomnia, and daytime somnolence.…”
Section: Introductionmentioning
confidence: 99%
“…The level of fatigue is similar in studies comparing European to U.S. patients, even though the clinical features and treatment of these two groups was different (108). Fatigue was demonstrated to be more severe in patients with pulmonary disease plus extrapulmonary disease than in those with pulmonary disease alone (109). Fatigue can affect overall patient health.…”
Section: Therapymentioning
confidence: 99%
“…Extrapulmonary sarcoidosis may be on occasion life threatening and may also affect the therapeutic approach 9 . There is also evidence that patients with pulmonary plus extrapulmonary sarcoidosis are more impaired in the severity of symptoms, restrictions of activities of daily living and there is also impairment of health status comparing to the patients with isolated pulmonary sarcoidosis 10 . One may therefore expect that pulmonary sarcoidosis differ in clinical and laboratory parameters from those patients with accompanied extrapulmonary sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%